2007
DOI: 10.15666/aeer/0601_129138
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Economic and Environmental Indicators in the Assessment of Desertification Risk: A Case Study

Abstract: Abstract. Desertification involves many countries featuring different ecological, economic, and social conditions. In Mediterranean Europe, high human pressure, economic development, and climatic changes combine to produce land consumption, soil erosion, salinization, and fire risk, all considered as key factors to start desertification processes. For many years the term desertification has been strictly associated to geo-physical conditions, but in very complex ecosystems the study of the interaction of physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 16 publications
1
56
0
Order By: Relevance
“…Based on the scores of the most important factors, prefectures were mapped into different groups. Entities (agricultural land-use classes and provinces) placed close each other in the factorial plane indicate spatial convergence [33,87].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the scores of the most important factors, prefectures were mapped into different groups. Entities (agricultural land-use classes and provinces) placed close each other in the factorial plane indicate spatial convergence [33,87].…”
Section: Discussionmentioning
confidence: 99%
“…Thus the importance of establishing environmental indicators to monitor degradation, rehabilitation, and sustainability of ecosystems and conditions [205] as well as prediction models that consider both ecological and human variables is clear [206]. The development of indicators that represent an integration of economic, social, and environmental dimensions of dryland development is a major challenge, and requires a robust foundation [207]. The team of researchers involved in this review supports the development of common but flexible indicator sets to assess long-term progress towards the environmental, economic, and social benefits of SLM practices.…”
Section: Academiamentioning
confidence: 99%
“…As an important natural selection pressure of plant distribution in desert areas, desertification plays an important role on the community succession (Maun, 1998; Peng et al, 2012; Salvati et al, 2008). Some studies showed that sand burial can enhance the seed germination and seedling emergence of the sand-burial tolerant shrubs Wang et al, 2013).…”
Section: Spatial Associationmentioning
confidence: 99%